Genome-Wide Association Study of Resistance to Pseudomonas syringae in the USDA Collection of Citrullus amarus - Rennberger, Gabriel (Plant disease, 2023)
Pseudomonas leaf spot (PLS), caused by Pseudomonas syringae pv. syringae, is an emerging disease of watermelon in the United States with the potential to severely reduce yield under humid conditions. The genetic basis of resistance to this disease is not known and no resistant germplasm is available. Because Citrullus amarus is an important reservoir of resistance genes for the cultivated watermelon, C. lanatus, we screened the United States Department of Agriculture plant introduction collection of C. amarus for resistance to PLS. Accessions (n = 117) were phenotyped for their level of resistance to PLS in two separate tests. Accession means of percent leaf area affected ranged from 1.5 to 99.4%. The broad-sense heritability for the trait was 0.51. Whole-genome resequencing generated 2,126,759 single-nucleotide polymorphisms (SNPs) which were used to perform a genome-wide association study (GWAS) aimed at discovering molecular markers for resistance. Three different models-BLINK, FarmCPU, and MLM-were included in the GWAS analyses. BLINK and FarmCPU, which are multilocus models, found eight SNPs, located on chromosomes Ca01, Ca05, Ca06, Ca08, and Ca10, that were significantly associated with resistance to PLS. Two of these SNPs were found by both BLINK and FarmCPU. The MLM model did not detect any significant associations. BLINK and FarmCPU estimated an explained phenotypic variance of 43.6 and 28.5%, respectively, for SNP S6_19327000 and 25.0 and 26.0%, respectively, for SNP S1_33362258, the two most significant SNPs found. In total, 43 candidate genes with known involvement in disease resistance were discovered within the genomic intervals of seven of the eight peak SNPs. Eleven of the candidate genes that were found have been reported to be involved in resistance to P. syringae in other plant species. Two significant SNPs were within resistance genes previously documented to play important roles of plant resistance specific to P. syringae in other pathosystems. The SNPs identified in this study will be instrumental in finding causal genes involved in PLS resistance in watermelon and developing resistant germplasm through breeding